BEBERAPA VARIABEL YANG MEMPENGARUHI KEPUASAN KONSUMEN - IING SRI HARDININGRUM; BENY MAHYUDI (STIE Indonesia Malang, 2022)
This study analyzes several variables that affect consumer satisfaction at the Gambir Tiga Putri Kediri Cracker Company. Some of these variables are consumer confidence and customer satisfaction. By analyzing a sample of 86 consumers who bought Gambir Crackers from the Tiga Putri Kediri company and analyzed using multiple linear regression, the results showed that consumer trust had a significant effect on consumer loyalty by 0.257, and consumer satisfaction influenced consumer loyalty by 0.525. The results of the analysis also show a coefficient of determination of 0.833 which means that consumer confidence and customer satisfaction have a significant effect on consumer loyalty.Keywords: consumer trust, consumer satisfaction, consumer loyalty